The Major Open Reading Frame of the β2.7 Transcript of Human Cytomegalovirus: In Vitro Expression of a Protein Posttranscriptionally Regulated by the 5′ Region - Bergamini, Giovanna (American Society for Microbiology, 1998)
β2.7 is the major early transcript produced during human cytomegalovirus infection. This abundantly expressed RNA is polysome associated, but no protein product has ever been detected. In this study, a stable peptide of 24 kDa was produced in vitro from the major open reading frame (ORF), TRL4. Following transient transfection, the intracellular localization was nucleolar and the expression was posttranscriptionally inhibited by the 5′ sequence of the transcript, which harbors two short upstream ORFs.